Extramacrochaetae regulates Notch signaling in the Drosophila eye through non-apoptotic caspase activity - Sudershana Nair; Nicholas E Baker (eLife)
Many cell fate decisions are determined transcriptionally. Accordingly, some fate specification is prevented by Inhibitor of DNA-binding (Id) proteins that interfere with DNA binding by master regulatory transcription factors. We show that the Drosophila Id protein Extra macrochaetae (Emc) also affects developmental decisions by regulating caspase activity. Emc, which prevents proneural bHLH transcription factors from specifying neural cell fate, also prevents homodimerization of another bHLH protein, Daughterless (Da), and thereby maintains expression of the Death-Associated Inhibitor of Apoptosis (diap1) gene. Accordingly, we found that multiple effects of emc mutations on cell growth and on eye development were all caused by activation of caspases. These effects included acceleration of the morphogenetic furrow, failure of R7 photoreceptor cell specification, and delayed differentiation of non-neuronal cone cells. Within emc mutant clones, Notch signaling was elevated in the morphogenetic furrow, increasing morphogenetic furrow speed. This was associated with caspase-dependent increase in levels of Delta protein, the transmembrane ligand for Notch. Posterior to the morphogenetic furrow, elevated Delta cis-inhibited Notch signaling that was required for R7 specification and cone cell differentiation. Growth inhibition of emc mutant clones in wing imaginal discs also depended on caspases. Thus, emc mutations reveal the importance of restraining caspase activity even in non-apoptotic cells to prevent abnormal development, in the Drosophila eye through effects on Notch signaling.